American Economic Journal: Macroeconomics - Rogerson, Richard (American Economic Review, 2016)
The American Economic Journal: Macro economics was established in 2007 along with three other field journals focusing on micro economics, applied economics, and economic policy. As stated in the call for papers and on the jour nal Web site, AEJ: Macroeconomics focuses on studies of aggregate fluctuations and growth, and the role of policy in that context. Such studies often borrow from and interact with research in other fields, such as monetary theory, industrial organization, finance, labor economics, political economy, public finance, international econom ics, and development economics. To the extent that they make a contribution to macroeconom ics, papers in these fields are also welcome. The first order of business before the jour nal went into operation was the recruitment of a Coeditor. I was delighted that Steve Davis (University of Chicago) agreed to join. Steve and I have worked extremely well together. The second order of business was the recruit ment of members of the Board of Editors. This turned out to be easier than I expected, as nearly all the researchers we approached agreed to join. The Board of Editors consists of: Mark A. Aguiar (University of Rochester), Nick Bloom (Stanford University), Pierre Cahuc (Paris Pan theon), John Campbell (Harvard University), Yongsung Chang (University of Rochester), John H. Cochrane (University of Chicago, GSB), William Easterly (New York University), Jordi Gali (CREI), Martin Eichenbaum (Northwestern University), Erik Hurst (University of Chicago, GSB), Charles I. Jones (University of California, Berkeley), Anil Kashyap (University of Chicago, GSB), David Laibson (Harvard University), Jonathan A. Parker (Northwestern University), Maurice Obstfeld (University of California, Berkeley), Thomas Philippon (New York Uni versity), Chris Pissarides (London School of Economics), Valerie A. Ramey (University of California, San Diego), Christina D. Romer (Uni versity of California, Berkeley), David Romer (University of California, Berkeley), Thomas J. Sargent (New York University), Mark W. Watson (Princeton University), Ivan Werning Report of the Editor